ANALISI BEBAN DAN INDEKS PENCEMARAN DI TINJAU DARI PARAMETER LOGAM BERAT DI SUNGAI SIAK KOTA PEKANBARU - Yanti Agustina; Bintal Amin; Thamrin Thamrin (Jurnal Ilmu Lingkungan, 2012)
Study on the pollution load index by means of heavy metal parameter in Siak river of Pekanbaru City has been conducted from February to May 2012. Samplings were conductedat two sites which were considered to have different input of pollutants. The heavy metalsstudied were Pb, Cu and Zn. The results showed that almost all water quality parameters,with the exception of zinc in Station 1, have exceeded the quality standards according to PP.82/2001 Republic of Indonesia for Class I and II. Estimated Pb load amounted to 889.55tons/month, Zn 737.10 tons/month and Cu of 726.37 tons/month. Referring to the index ofheavy metal contaminants Pb, Cu and Zn by Kep Men LH No. 115/2003, it is suggested that the condition of Siak River in Pekanbaru City especially at Station 1 was slightly polluted whilest Station 2 was considered as heavily polluted and could be harmful when used as araw material for drinking water as well as for recreation facilities, aquaculture, livestock andfor agriculture irrigation.